Nie tylko muzyczna droga wirtuoza. O młodości, dorastaniu i życiowej klęsce Romualda z Książki pamiątek Narcyzy Żmichowskiej - Łuczak, Bartłomiej (Starość i młodość w literaturze i kulturze, 2016)
This article in its interpretative nature offers a glance at the adolescent years of the main characterof the novel, a gifted violinist Romuald. The focus of this insight is placed on the motivation behind thelife choices of the virtuoso, including choice between the opportunity to experience fulfilled love and the drive to achieve fame resulting from the commitment to the musical career. The article sketches the psychological portrait of the character, which takes into account changes undergoing within his inner self, in his attitude towards others, as well as in his treatment of music and the violin itself. Light is particularly cast on Romuald, his attitude towards music and his own career at the time of experiencing a growing feeling towards Helusia, a young daughter of a craftsman. The last part of the article deals with psychological and moral dimension of decision made by Helusia, a character who decides to abandon Romuald after learning the truth about his past.